Women's views on lifestyle changes to reduce the risk of developing Type 2 diabetes after gestational diabetes: a systematic review, qualitative synthesis and recommendations for practice. Issue 6 (4th March 2019) - Dennison, R. A.; Ward, R. J.; Griffin, S. J.; Usher‐Smith, J. A.
Abstract: Aims: After gestational diabetes, many women exhibit behaviours that increase their risk of developing Type 2 diabetes. We aimed to systematically synthesize the literature that focuses on the views of women with a history of gestational diabetes on reducing their risk of developing diabetes postpartum through lifestyle and behaviour changes. Methods: We identified qualitative studies that examined the views of women with a history of gestational diabetes towards healthy eating and physical activity, Type 2 diabetes risk management or their experience of a diabetes prevention programme, and conducted a thematic synthesis to develop descriptive and then analytical themes. We also evaluated the quality of each study and the confidence that we had in our findings. Results: We included 21 articles after screening 23 160 citations and 129 full texts. We identified six themes of interacting influences on postpartum behaviour: role as mother and priorities; social support; demands of life; personal preferences and experiences; risk perception and information; and finances and resources (plus preferred format of interventions). These factors inhibited many women from addressing their own health, while they motivated others to persevere. We also developed 20 recommendations, most with high or moderate confidence, for effective promotion of healthy lifestyles in this population. Conclusions: Many factors hinder healthy lifestyles after gestational diabetes, yet how women interpret them can motivate or prevent changes that reduce diabetes risk. As our recommendations emphasize, women's experiences and needs should be considered when designing strategies to promote healthier lifestyles in this population. What's new?: After having had gestational diabetes, many women do not adopt healthy lifestyles that would reduce their risk of developing Type 2 diabetes. We found, in summary, that women identified themselves primarily as mothers who prioritized their family above themselves, and needed resources, time, energy, information and support to encourage healthy diets and levels of activity. Based on these findings, we developed 20 recommendations for effectively promoting healthy lifestyle in this population. These recommendations highlight the need for interventions to be centred on women's needs and experiences.